Presenilin1 FAD mutants and γ‐secretase inhibitors decrease VEGFR2 signaling and block angiogenic functions of brain endothelial cells. (20th December 2022) - Pandey, Rukmani; Robakis, Nikolaos K; Georgakopoulos, Anastasios
Abstract: Background: Alzheimer's disease (AD) is a multifactorial and progressive neurodegenerative disease where cerebrovascular abnormalities are commonly observed. Various factors, including decreased sprouting angiogenesis, can cause a reduction in capillary density observed in AD. In addition, brain vascular alterations occur before the appearance of neuropathology in animal AD models. Brain angiogenesis is a reparative function in response to toxic insults and is regulated by endothelial cells (ECs) and angiogenic factors such as the VEGF; impairment in this function would render the brain vulnerable to insults. In present study, we examine the effects of Presenilin 1 (PS1)‐Familial AD (FAD) mutants and γ‐secretase in the VEGF‐induced angiogenic signaling and functions of brain ECs. Method: Primary cortical ECs (pCECs) from brains of wild‐type (WT) and knock‐in (KI) mice expressing either PS1 M146V or PS1 I213T FAD mutant in heterozygous state were isolated and cultured. These mice constitute a "humanized" FAD model having the same genotype as human FAD patients. We performed the in vitro angiogenesis assays using pCEC cultures. Processing of VEGFR2 was detected in HEK293 cells overexpressing VEGFR2 in the presence or absence of VEGF‐A and γ‐secretase inhibitor (RO4929097). The same processing was also analyzed by western blotting in PS1 M146V and I213T mutant pCECs treated with VEGF‐A. VEGF‐induced phosphorylation of signaling molecules downstream of VEGFR2 such as p38 kinase and PLCγ1 was also examined in WT and PS1 M146V mutant pCECs by western blotting. Result: We found that VEGFR2 is processed by γ‐secretase and that this processing together with VEGF‐induced sprouting, tube formation, migration and angiogenic complexes between VE‐cadherin and Rok‐α kinase are decreased in the presence of γ‐secretase inhibitor or by PS1 FAD mutants. Furthermore, the VEGF‐induced phosphorylation of p38 and PLCγ1 is decreased in PS1 FAD mutant pCECs. Conclusion: Our findings suggest that VEGFR2 is processed by γ‐secretase and that γ‐secretase promotes VEGF‐induced angiogenic functions of brain ECs through activation of VEGF‐VEGFR2 downstream signaling. Our data also show that a PS1 FAD mutant decreases both the VEGFR2 processing by γ‐secretase and the VEGF‐induced signaling and angiogenic functions of pCECs, providing a mechanism via which FAD mutants affect brain angiogenesis.